CLINICAL STUDY ON MEDOROGA WITH SPECIAL REFERENCE TO VISESHA BY YAVAMALAKA CHURNA - Ishwar Chandra, Rai; Mahendra, Singh; Kavitha, M.; Richa, Singh; Shardul Vikram, Singh (International Journal of Ayurveda and Pharma Research, 2015)
The present era termed as age of Machines and Materialism has led to global economic advancement and affluence brought a drastic change in the life styles and living environment. Change in food habits, sedentary work, stressful environment etc. are the gifts of Industrialization to mankind. One side of life is happy with reduced physical activity and fat rich tasty food but the other side is showing affliction to chronic lifestyle disorders like diabetes mellitus, hypertension, cancer, ischemic heart disease, cerebro-vascular accidents, atherosclerosis, varicose veins etc. These diseases have been recognized as the leading killers of the millennium. Obesity is traced to be a major risk factor for these diseases. This study includes evaluate the applicability of concept of Visesha in Medoroga and clinical study on management of Medoroga by using Yavamalaka churna with special reference of Prakopana viparyayo hi dhatunam prasham karanam iti. Considering the above problem this study was planned the concept of Prakopana viparyayo hi dhatunam prasham karanam iti in the management of Medoroga with Yavamalaka churna because Medo dhatu is snigdha and guru in nature while Yava (Hordeum vulgarae) is Ruksha and Aguruand Amalaki (Emblica officinalis) also Ruksha in nature. The Amalaki has Tridoshahara properties especially Medohara. So these two drugs have opposite properties to medo dhatu. Hence due to the concept of Prakopana viparyayo hi dhatunam prashama karanam iti, yava and Amalaki cause the Hrasa of Medo dhatu.